STUDI PERBANDINGAN TEPUNG BERAS DAN TEPUNG TAPIOKA PADA PEMBUATAN KERIPIK KULIT SINGKONG - Wahyuni, Indah Fitri; Dasir, Dasir; Muchsiri, Mukhtarudin (Universitas Muhammadiyah Palembang, 2013)
This research aims to study the ratio of rice flour and tapioca flour in the manufacture of leather cassava chips produced. This research has been conducted in the laboratory of the Faculty of the University of Muhammadiyah Palembang Pertanin in January to March 2012. This research used Randomized Block Design (RBD) are arranged in a non-factorial combinations of five treatment and repeated five times, with each factor treatment T1 (90% rice flour and tapioca flour 10%), T2 (rice flour 80 % and 20% starch), T3 (70% rice flour and tapioca flour 30%), T4 (60% rice flour and tapioca flour 40%) and treatment T5 (50% rice flour and tapioca flour 50%). Parameters observed in this study, to include the chemical analysis of water content and carbohydrate content. organoleptic tests include flavor and color to the test level of preference and level of crispness to the test ranking. While the physical analysis of volume shrinkage. The results showed that the highest water content contained in the treatment T5 (50% rice flour and tapioca flour 50%) with an average value of 3.438% and the lowest water content at T1 treatment (90% rice flour and tapioca flour 10%) with a mean value average 2.160%. Comparison of the type of flour used can affect carbohydrate content of cassava chips on the skin. Treatment T1 (90% rice flour and tapioca flour 10%) had the highest carbohydrate content than other treatments. Treatment T2 has the highest level of preference for flavor chips cassava peel treatment than T3, T1, T4 and T5. T2 treatment is treatment with an optimal ratio of flour. Treatment T2 (80% rice flour and tapioca flour 20%) had the highest level of preference for color chips cassava peel treatment than T3, T1, T4 and T5. Because rice flour has a higher protein content than starch. Treatment T2 (80% rice flour and tapioca flour 20%) had the highest level of crispness in the skin of cassava chips than treatment T3, T1, T4 and T5. Rice flour is used can affect the crispness of the skin cassava chips. Comparison of the type of flour used can affect the volume shrinkage in the skin of cassava chips. Treatment T1 (90% rice flour and tapioca flour 10%) had the lowest shrinkage volume compared to other treatments.